Ultrasonic techniques for detection of thinning defects in metal plates - Hrairi, Meftah; Zuhudi, Nurul Farahana (2010)
This paper describes the use of ultrasonic nondestructive evaluation in corrosion detection of aircrafts structures. Initiating on the inside or in the interface of an aircraft’s skin, the corrosion must be tested from the outside surface. Corroded aluminum as well as corrosion simulation samples were inspected using pulse-echo technique of ultrasonic nondestructive evaluation and the values of the remaining thickness obtained was compared with the noncorroded plate of the same type of aluminum alloy. Surface roughness of those plates was also investigated to establish its relation with the determined remaining thicknesses. The estimated depth of the real corrosion by this method shows good agreement with that measured with a micrometer.